1112 Trazodone responsive Agrypnia. (27th April 2018) - Hernandez, Meylin Lam; Dredla, Brynn K; Castillo, Pablo R
Abstract: Introduction: Creutzfeldt-Jakob disease (CJD) is a neurodegenerative, rapidly progressive dementia caused by accumulation of misfolded prion protein that progresses inexorably to fatality. Sleep symptoms are not viewed as cardinal symptom of CJD, and little is reported. We describe a unique case of CJD with early insomnia responsive to trazadone. Report of Case: 48-year-old African American lady referred to sleep clinic for insomnia. Symptoms developed six months prior to presentation. The insomnia was with sleep initiation and maintenance. She previously trialed zolpidem and eszopiclone, without benefit and experienced agitation and balance disturbances. Decreased dreaming accompanied insomnia onset. She denied snoring, parasomnias, restless leg syndrome, circadian dysrhythmia. No alcohol abuse but smoker. Only medication was esomeprazole. After the development of insomnia, she experienced muscle spasms, irritability, and gait impairment. Physical examination revealed mild hypomimic facial expression, bilateral hyperreflexia in lower extremities, ataxic and broad-based gait. Overnight oximetry within normal limits. Brain MRI images showed changes affecting basal ganglia consistent with prion disease. She was given trazadone 50 mg up titrated to 150 mg. At follow up she reported good response (total sleep time of 4 hours), rested upon awakening. A polysomnogram was suggested to document sleep architecture disintegration distinctive of prion diseases but she declined. Patient subsequently progressed and died. Autopsy was confirmatory for CJD. Conclusion: We describe a novel case where insomnia was an initial non-motor manifestation of CJD effectively treated with trazadone. Previous cohort study about sleep pathology in CJD showed 90% of patient having at least one sleep-related complaint at the time of presentation, insomnia being the most prevalent. However, there is no evidence on pharmacological treatment of insomnia linked to prion diseases. This case highlights the role of trazadone treating organic insomnia and opens a new research path to understand the neurophysiology behind its effect.